Exploring the Leadership Role of the Chair of the FISIP Student Executive Board University Muhammadiyah Indonesia (UNISMA Bekasi) in Encouraging Innovation and Creativity of Management - Astia Salsabil; M. Yoga Chossy Pratama; Aos Kuswandi (Journal of Economics, Management, Development, and Education, 2026)
This study aims to explore the leadership role of the Chairperson of the Student Senate (SEMA) of the Faculty of Social and Political Sciences (FISIP), University of Muhammadiyah Indonesia (UNISMA) Bekasi), in encouraging innovation and creativity among its board members. The study employed a qualitative approach with an exploratory method. Data were collected through interviews with the Chairperson and an active board member, supported by organizational observations. The findings reveal that the Chairperson plays a significant role in creating an organizational climate that supports innovation and creativity through open communication, motivation, appreciation of new ideas, and involving members in decision-making processes. Board members felt they were given opportunities to express opinions and develop their ideas. Although several obstacles were identified, such as limited time due to academic responsibilities and a lack of self-confidence among some members, the Chairperson is continuously sought to address these challenges through effective coordination and ongoing support. Therefore, the leadership of the Chairperson of SEMA FISIP Universitas Muhammadiyah Indonesia (UNISMA Bekasi) significantly contributes to fostering innovation and creativity among organizational members.